Isolation, Characterization, and Identification of Biosurfactant-Producing Bacteria from Palm Oil Mill Effluent - Jezila Amana Nousra Atsemani; Nisa Rachmania Mubarik; Yuliana Maria Diah Ratnadewi (Institut Pertanian Bogor, 2026)
Biosurfactants-producing bacteria are bacteria with the ability to produce natural surfactants that can degrade oil both in soil and water. Most of these biosurfactant-producing bacteria are often found in area polluted by grease or oil like palm oil mill effluent. The purpose of this research was to isolate, characterize, and identify biosurfactant-producing bacteria from palm oil mill effluent. This research was conducted using descriptive and identification methods through a general screening using oil displacement, drop collapse, and hemolysis assay, morphological characterization, emulsification tests and molecular identification for the bacteria with the highest emulsification index. Bacteria were isolated from palm oil wastewater by dilution method. In this study, 17 isolates were obtained with 2 isolates having the highest oil spreading results (SLP2.2 and SLP1.5). Both isolates showed negative hemolysis activity and were both identified as Gram-positive bacilli. Both isolates were cultivated for biosurfactant production and subsequent extraction. Crude biosurfactant extract was successfully obtained from isolate SLP2.2 with a yield of approximately 0.08 g/L. Emulsification index value of SLP2.2 extract was 36.93 ± 0.57%. SLP2.2 was identified as Cytobacillus kochii. This research provides microbial resources for microbial enhanced oil recovery and lays a foundation for practical application, such as sustainable bio-based products development.